Learning Strategies at SD Muhammadiyah 1 Wringinanom During the Covid-19 Pandemic - Citra Dwi Yanti; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The purpose of this study was to determine the strategy pf SD Muhammadiyah 1 Wringinanom in learning the during the covid 19 pandemic. This scientific work provides various aspects : including the history of the establishmentof SD Muhmmadiyah 1 Wringinanom and the learning system used during the covid – 19 pandemic. This scientific paper examines various aspects used during the covid 19 pandemic. This research is a descriptive qualitative research using research data collection techniques through interviews, documentation and observation. Based on the result of research at SD Muhammadiyah 1 Wringinanom learning using an online system until now the school has not dared to do face to face learning. The impact that has arisen due to the covid pandemic on education has made the educational system and curriculum change the educational curriculum to be more streamlined while not burdening students. In addition to the negative impacts there are positive impacts, including 1) Online learning application innovation 2) Teachers are not ignorant of technology 3) The occurrence of teacher and student collaboration.